Quality Effort Strategy of O2O Takeout Service Supply Chain under Three Operation Modes - Peng Xing; Junzhu Yao; Meixia Wang (Complexity)
This paper investigates channel selection and quality effort in O2O takeout service supply chain consisting of a takeout platform, a catering business, and a distribution rider. By analyzing the three operation modes of platform distribution, business self-distribution, and business self-built platform + distribution, the profit functions of O2O takeout service supply chain members are constructed, respectively. On the basis of game theory, the optimal quality effort and profits are obtained. Combined with numerical simulation, the effects of revenue sharing rate and market size on the optimal quality effort and profits under different scenarios are discussed. The results reveal that O2O takeout platform should cooperate with more catering businesses, and adopt appropriate strategies considering different market sizes of catering businesses. Additionally, the catering business should properly consider the market size and adopt different online and offline prices. Meanwhile, the rider should choose a reasonable quality effort according to the revenue sharing rate.